MENDAPATKAN LOYALITAS PELANGGAN MELALUI GAMIFIKASI : A SYSTEMATIC LITERATURE REVIEW - Hermanto, Hermanto; Aris Rinandy, Alditya (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This research aims to evaluate the role of relationship between gamification and customer loyalty through a Systematic Literature Review approach. The SLR stages applied include formulating research questions, conducting a literature search using Google Scholar and ScienceDirect, screening based on inclusion–exclusion criteria, and assessing article quality. The initial identification process yielded 318 national and international indexed articles published between 2020–2025. After a series of screening steps, 18 articles relevant to gamification and customer loyalty were selected for descriptive analysis. The findings indicate that gamification has a positive and significant effect on customer loyalty, and this influence becomes stronger when user engagement functions as a mediator. Gamification elements such as points, rewards, badges, and leaderboards are shown to enhance intrinsic motivation, enjoyable user experience, and emotional attachment to digital platforms, which subsequently encourage repeat purchases, user recommendations, and brand commitment. Thus, user engagement serves as an essential psychological mechanism that connects game-based experiences with the formation of customer loyalty. Future studies are recommended to expand sample contexts, consider demographic and cultural factors as moderating variables, and employ longitudinal methods to obtain a more comprehensive understanding of loyalty dynamics driven by gamification.